Perspectives on trauma-informed maternity care for those with a history of child sexual abuse - Elsa Montgomery; Lucy Duckworth (Frontiers in Global Women's Health)
Failure to listen has been a recurrent issue for recent users of maternity services in the UK. The need to listen to women has been recognised in successive reports. Listening is particularly difficult when the population is unheard such as those who have experienced child sexual abuse. Despite its prevalence and lasting impact on physical and mental health, care of women who have experienced child sexual abuse is not usually part of healthcare professional or student education. This paper discusses the benefits of trauma-informed care to meet the needs of survivors of child sexual abuse. It also discusses the co-production of an e-resource on trauma-informed care for women and birthing people who have experienced child sexual abuse. The resource addresses the related educational gap for healthcare professionals and enables the powerful words of this silent, hidden population to be heard.